2019
DOI: 10.1007/s10792-019-01126-4
|View full text |Cite
|
Sign up to set email alerts
|

Results of pars plana vitrectomy for primary rhegmatogenous retinal detachment with PVR grades A and B in high-myopic eyes

Abstract: Purpose To evaluate the results of pars plana vitrectomy (PPV) without adjuvant buckling procedures for the primary rhegmatogenous retinal detachment (RRD) with PVR grades A and B in high-myopic eyes. Methods A retrospective review included 291 eyes treated for primary RRD from 2008 to 2016. The single surgery success rate (SSSR), the total number of surgeries, outcomes and complications were analysed between group of 67 eyes with high axial myopia (group A) and group of 224 eyes without high myopia (group B).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Because of anatomical characteristics, RRD surgery is challenging in eyes with high myopia; the SSAS rate in such eyes is reportedly lower than the SSAS rate in nonmyopic eyes. Janco et al [ 29 ] found that the anatomical success of primary PPV for RRD did not differ between eyes with and without high myopia in patients with PVR grade A or B; however, only four (1.4%) patients underwent PPV with air tamponade in their study. In our study, 30 (37.03%) patients had axial length > 26 mm (range, 22.46–32.78 mm; mean, 25.52 mm); four of seven cases of retinal redetachment had high myopia with axial length ranging from 26.03 to 30.21 mm.…”
Section: Discussionmentioning
confidence: 83%
“…Because of anatomical characteristics, RRD surgery is challenging in eyes with high myopia; the SSAS rate in such eyes is reportedly lower than the SSAS rate in nonmyopic eyes. Janco et al [ 29 ] found that the anatomical success of primary PPV for RRD did not differ between eyes with and without high myopia in patients with PVR grade A or B; however, only four (1.4%) patients underwent PPV with air tamponade in their study. In our study, 30 (37.03%) patients had axial length > 26 mm (range, 22.46–32.78 mm; mean, 25.52 mm); four of seven cases of retinal redetachment had high myopia with axial length ranging from 26.03 to 30.21 mm.…”
Section: Discussionmentioning
confidence: 83%
“…10 Patolojik miyopili hastalara uygulanan VRC'lerde; Demircan ve ark.nın yaptığı çalışmada %80, Janco ve ark'nın yaptığı çalışmada %82,1, Cheng ve ark.nın yaptığı çalışmada %86,5 oranlarında anatomik başarı saptanmıştır. [16][17][18] Yaptığımız çalışmada, %86,9 oranında tek cerrahi ile retina yatışıklığı sağladık. Nüks RD gelişen olgularda 2.…”
Section: Discussionunclassified